Expression of concern from the editors in chief: “A $Γ $-convergence result for optimal design problems” - Coron, Jean-Michel; Ghys, Étienne; Saint-Raymond, Laure (Comptes Rendus. Mathématique)
This note provides a warning about “A $Γ $-convergence result for optimal design problems” by Hamdi Zorgati published online in Comptes Rendus Mathématique on 04 October 2022, Tome 360 (2022), pp. 1145-1151, https://doi.org/10.5802/crmath.375.